'They said it was bronchiolitis; is it going to turn into asthma doctor?'. Issue 8 (19th August 2014) - Gidaris, Dimos; Urquhart, Don; Anthracopoulos, Michael B.
Abstract Acute bronchiolitis is a common paediatric disease of infancy. Its association with subsequent asthma development has puzzled clinicians and epidemiologists for decades. This article reviews the current state of knowledge regarding the role of acute bronchiolitis in the inception of asthma. There is little doubt that acute bronchiolitis is associated with an increased risk of recurrent wheezing throughout the primary school years although the direction of causality—i.e. whether bronchiolitis in infancy leads to asthma or it merely represents the first clinical presentation of predisposition to asthma—is uncertain. Existing evidence suggests that both host factors (e.g. prematurity, atopic predisposition) and acute viral infection characteristics (e.g. type of virus, severity) are operating in this relationship, perhaps with variable involvement in different individuals. Further clarification of these issues will help paediatricians provide evidence‐based information regarding the long‐term prognosis of this common disease to the families, and at the same time, it will facilitate prophylactic approaches and therapeutic strategies.